Using Different Types of Fertilization for Increasing Sugar Beet Growth under Sandy Soil Conditions. - M. S. Zaki; Eman I. El-Sarag; Howaida A. Maamoun; M. H. Mubarak (Journal of Plant Genetics and Crop Research, 2018)
Four nitrogen forms and four biofertilizer were application as well as their interactions on growth analysis of sugar beet (Beta vulgaris L). The important results could be summarized as follow. Urea treatment achieved maximum increase in Leaf Area Index were 69.71, 81.32 and 166.54 at 120, 140 and 160 day in the 1st season, respectively, The highest one was 160.6 in the 2nd also was ammonium nitrate application at 160 days. Urea treatment inclusion in seeds with ntrobin application resulted the highest values of leaf area index (LAI), crop growth rate (CGR) and leaf area duration (LAD) and in the 1st season. A slight increase was 0.03 g/week in this case was found due to urea treatments as compared with the others treatment at the period from Relative growth rate (RGR3) in the 1st season. Ammonium nitrate treatment achieved the maximum values from Crop Growth Rate was 39.16 g/day in (CGR1), 93.24 and 13.5 g/day in (CGR2) and (CGR3) from urea treatment at the 1st season. The highest net assimilation rate was 0.66 g/dm.week achieved by ntrobin as compared the others treatment whereas, the lowest one 0.11 g.dm /week with the phosphorine application. Ammonium sulphate treatment with (phosphorin + ntrobin) obtained the highest net assimilation rate (NAR) in the 1st season. The highest values from leaf area duration were 0.11, 0.19 and 0.15 dm2/week achieved with urea and ntrobin in the 1st season at (LAD2), (LAD3) and (LAD4). Ammonium nitrate treatment with phosphorin obtained the highest leaf area duration (LAD) in the 2nd season. Generally, it could be recommended that fertilizing sugar beet plants variety Ymer with nitrogen forms inoculated with biofertilizer (ntrobin 600gm/fed) increased the growth of sugar beet plants under sandy soil conditions.
Keywords: Ammonium nitrate